Opto-mechanical systems design - Yoder, Paul R. (Optical engineering (Marcel Dekker, Inc.), 1993)
Presents an information on opto-mechanical systems design guidelines and their applications in real environments. This text emphasizes techniques for accomplishing design tasks. It outlines techniques for mounting various optical elements and groupings.